Komi – Russian and Karelian – Russian Code-Switching - A. A. Ershov; V. A. Ivanova; L. A. Ulianitckaia (Дискурс, 2023)
Introduction. The language situation in Russia is unique with a fair number of languages spoken on its territory and all of them having different status and scope of use. This implies the relevance of the study that focuses on the analysis of code-switching in the spoken language of the bilinguals speaking Komi and Russian and Karelian and Russian. The novelty of the study is implied by the analysis of the code-switching in the language pairs mentioned above. This contributes to the development of the code-switching theory.Methodology and sources. The methods of language data collection and processing are sociolinguistic methods of interviewing, questionnaire, observation, quantitative and descriptive methods. The research material are scripted dialogues with bilinguals as well as the “Komi mu” and “Parma gor” 2022 issues.Results and discussion. The study of the Komi-Russian and Karelian-Russian code-switching was conducted using P. Muysken’s topology of code-mixing. P. Muysken sees code-switching as alternation, insertion, and congruent lexicalization according to the degree of the foreign word assimilation in the matrix language. The features of the spoken language of the Komi-Russian bilinguals are the frequent use of Russian discursive and introductory lexical items and adverbs; the nouns and the adjectives usually following the grammatical rules of Komi; the respondents giving preference to Russian versions when using numerals. For the spoken language of the Karelian-Russian bilinguals it is typical to address to Russian vocabulary, especially when mentioning dates, numbers, and using introductory words and phrases; Russian words are also being quite easily transformed according to the Karelian grammar through its case system.Conclusion. Spontaneous speech of the bilingual interviewees contains a great number of code-switching, that could be a convincing demonstration of the language shift and is conditioned by a number of extralinguistic and linguistic factors, such as language prestige, language functionality, language situation, the native language of the interlocutor, and the willing of the respondent to use a certain language.